Sinophone Classicism: Chineseness as Temporal and Mnemonic Experience in the Digital Era - Yang, Zhiyi (The Journal of Asian studies, 2022)
In recent decades, highly heterogeneous literary and artistic articulations harking back to China's classical past have gained increasing currency in the global Sinophone space and cyberspace. Instead of dismissing them as “fetishisms” or authenticating them as “Chinese traditions,” I propose “Sinophone classicism” as a new critical expression for conceptualizing this diverse array of articulations. It refers to the appropriation, redeployment, and reconfiguration of cultural memories evoking Chinese aesthetic and intellectual traditions for local, contemporary, and vernacular uses, by agents identified or self-identified as Chinese. This essay proposes a subjective, intimate, and reflexive way to experience an individual's culturally acquired “Chineseness” that is temporal, mnemonic, and often mediated by digital media. It joins recent scholarly efforts to dismantle the view of “Chinese modernity” as a monocentric and homogenous experience by refocusing on classicism as a kind of “antimodern modernism.” It also joins the post-Eurocentric turn in global academia by hinting at a future of “global classicisms.”